RELIGIOUS MODERATION EDUCATION: GENERATION-Z AS AGENTS OF CHANGE IN A MULTICULTURAL SOCIETY - Fitrah Sugiarto; Nindyra Mei Devita; Umniati (Tahiro : Journal of Peace and Religious Mederation, 2024)
Generation Z has a strategic role as an agent of change in implementing the values of religious moderation in a multicultural society. This article aims to explore the importance of religious moderation education in equipping Generation Z to be able to play an active role in maintaining social harmony, preventing religion-based conflicts, and facing the challenges of the digital era that often raises the issue of intolerance. Through a descriptive-qualitative approach, this article analyzes the relevance of religious moderation in shaping inclusive, tolerant, and respectful attitudes among Generation Z. Holistic religious moderation education involving educational institutions, families, and digital media can be an effective solution in instilling the values of diversity and moral integrity. The results of the study show that Generation Z, with its adaptive characteristics and openness to change, has great potential to be a catalyst for the creation of a peaceful, fair, and harmonious society. Therefore, religious moderation education must be a priority in character development strategies to strengthen the role of Generation Z as guardians of harmony in a multicultural society.